Angled view of single storey houses, Balmain, Sydney, New South Wales, ca. 1970 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting weatherboard houses without front yard, overhanging eaves, two schoolgirls in photo.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions documentation, see file NLA09/703.
Wes Stacey reference number: 6 37 2.
Also available online
Keywords: Wooden-frame houses -- New South Wales -- Balmain -- Photographs; Windows -- New South Wales -- Balmain -- Photographs; School children -- New South Wales -- Balmain -- Photographs; Balmain (N.S.W.) -- Buildings, structures, etc. -- Photographs